INTEGRASI KODE ETIK GURU, ETIKA KEILMUAN, DAN TPACK DALAM PEMBELAJARAN SEJARAH KONTROVERSIAL - Maulana Fariqi Nuri (Jurnal Pendidikan Sejarah Indonesia, 2026)
This study aims to analyze the integration of teachers' code of ethics, scientific ethics, and Technological Pedagogical Content Knowledge (TPACK) in the teaching of controversial history. The background of this study stems from the challenges faced by history teachers in teaching sensitive historical materials, such as ideological, political, and social conflict issues, which demand a balance between moral, scientific, and pedagogical responsibilities based on technology. This study uses a literature study method (library research) with a descriptive qualitative approach through thematic analysis of various relevant scientific sources. The results show that teachers' code of ethics serves as a moral and professional foundation in managing ethical dilemmas in the classroom, scientific ethics maintains objectivity and academic integrity in the delivery of historical materials, while TPACK acts as a pedagogical framework that enables the use of technology to strengthen ethical and scientific values in the context of teaching controversial history. The integration of the three creates a paradigm for learning history that is critical, dialogical, and humanistic. This study suggests strengthening teacher professionalism based on ethics and educational technology. The limitations of this study lie in its conceptual approach without empirical field verification.